2007
DOI: 10.1002/jobm.200710317
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Pleurotus ostreatus fruiting body‐specific hydrophobin gene, Po.hyd

Abstract: Hydrophobins are a family of small, moderately hydrophobic proteins with eight cysteine residues arranged in a conserved pattern. A full-length cDNA, designated Po.hyd, corresponding to a hydrophobin gene of Pleurotus ostreatus was obtained in our previous work. The Po.hyd gene contains a 333 bp open reading frame (ORF), which is interrupted by two typical classI introns. There was no consensus signal for a polyA tail detected in the 3'untranslated region. However, an analogous T- or TG-rich motif was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…The expression of the hydrophobin 2 gene ( coh2 , CC1G_02185) was not detected in either developmental stage. These observations are consistent with previous findings in the mushrooms Lentinula edodes and Pleurotus ostreatus which employ two different sets of hydrophobin genes during fruiting body development [34,35]. These hydrophobins are thought to play alternative structural roles in the respective stages.…”
Section: Resultssupporting
confidence: 92%
“…The expression of the hydrophobin 2 gene ( coh2 , CC1G_02185) was not detected in either developmental stage. These observations are consistent with previous findings in the mushrooms Lentinula edodes and Pleurotus ostreatus which employ two different sets of hydrophobin genes during fruiting body development [34,35]. These hydrophobins are thought to play alternative structural roles in the respective stages.…”
Section: Resultssupporting
confidence: 92%
“…They can be arranged into distinct groups based on expression patterns. Previous studies reported a near complete turnover of hydrophobin genes from vegetative mycelium to fruiting body, indicating that two distinct sets of hydrophobins exist(Ma et al 2007; WW et al 2008; Cheng et al 2013a). We also observed that mycelium-expressed and fruiting body-expressed hydrophobins form distinct groups.…”
Section: Results: Developmentally Expressed Gene Classes In the Agari...mentioning
confidence: 98%
“…Fungal pheromone is responsible for initiating septal dissolution and clamp-cell fusion during the transition from monokaryotic to dikaryotic state, whereas hydrophobin regulates morphogenesis in fungi, particularly in fruiting body development of basidiomycetes [ 26 , 80 , 81 ]. It has also been reported that different sets of hydrophobins are employed by mushroom forming basidiomycetes in different developmental stages [ 81 , 82 ]. By contrast, most of the putative targets of cci-milR-13e-5p were related to macromolecule metabolism and protein binding.…”
Section: Discussionmentioning
confidence: 99%